Pengaruh Kunjungan Rumah oleh Perawat terhadap Tingkat Kepatuhan Pengobatan Penderita Pneumonia pada Balita di Wilayah Kerja Puskesma 2 Baturraden. - Triasih, Fajar; Istiawan, Rochani; Riyadi, Sugeng (Jurnal Keperawatan Soedirman, 2007)
Nurse home visiting program is very important for patient who suffered from pneumonia especially for children under five years old. This program can influence patient compliance during pneumonia treatment. Pneumonia cases have reached second rank most cases diseases in Banyumas regency. Therefore, nurse home visiting program become the main issues for treatment compliance for children who suffered for pneumonia. This research objective was to know the influence of nurse home visiting program to pneumonia patient treatment compliance of children less than five years old upon Baturraden II Puskesmas. This research was quasi experimental, with pre- post test non randomized control group design. Sample within this research was children under five years old who suffered from pneumonia upon Baturraden II Puskesmas. Mc Nemar test used to evaluate the impact of treatment in relation to compliance level. Meanwhile, the impact of nurse home visiting program to pneumonia patient compliance used Chi Square test with Y rates Correction, with Confident Interval 95% (a 0.05). Mc Nemar test shows that there was significant relationship of compliance level before and after treatment for experimental groups On the other hand, control group shows no significant different between pre and post test result. . Chi Square test with confident interval 95% (a 0.05) could be concluded that there are an influence nurse home visiting program to pneumonia patient treatment compliance with Significance value for 0.01.